Branch Leadership Optimization Performance in Improving The Performance of Government Banks In West Java - Samudra , Azhari Aziz; Zainal, Veithzal Rival; Koto , Eryus Amran; Hakim, Aziz; Nazriah, Ainun; Subagja, Iwan Kurniawan (Archives of Business Research, 2019)
As part of finance, every bank, mostly from the government, has an important role in supporting the country’s economic recovery from the crisis. The facts show that bank branches are the spearhead of bank operations which are very important in achieving bank goals. That is why every bank branch manager plays an important role in the overall success of the bank’s business. The purpose of this study is to analyze several factors that support the optimization of the performance of branch managers of government banks. The results showed that the work of branch managers of state-owned banks affected the performance of Government Banks in West Java.